2003
DOI: 10.1016/j.visres.2003.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial summation of S-cone ON and OFF signals: Effects of retinal eccentricity

Abstract: We studied spatial summation for S-cone ON and OFF signals as a function of retinal eccentricity in human subjects. S-cone isolation was obtained by the two-colour threshold method of Stiles, modified by adding blue light to the yellow background. Test stimuli were blue light increments or decrements within a circular area of variable size. These were presented for 100 ms at 0 to 20 deg along the horizontal temporal retinal meridian. Ricco's area of complete spatial summation was measured from the threshold vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
5
29
0
Order By: Relevance
“…As far as one could judge from their Figure 9, Ricco's area increased at a higher rate than the dendritic field size of the small bistratified cells (SBCs) known until recently as the only S-cone ON cells (Dacey & Lee, 1994). In the second study, Vassilev, Mihaylova, Racheva, Zlatkova, and Anderson (2003) confirmed this finding for the temporal horizontal retinal meridian. Volbrecht et al (2000) found it Bdifficult to conclude whether Ricco's area for the S-cone mechanism is directly related to dendritic field size [.…”
Section: Introductionmentioning
confidence: 53%
“…As far as one could judge from their Figure 9, Ricco's area increased at a higher rate than the dendritic field size of the small bistratified cells (SBCs) known until recently as the only S-cone ON cells (Dacey & Lee, 1994). In the second study, Vassilev, Mihaylova, Racheva, Zlatkova, and Anderson (2003) confirmed this finding for the temporal horizontal retinal meridian. Volbrecht et al (2000) found it Bdifficult to conclude whether Ricco's area for the S-cone mechanism is directly related to dendritic field size [.…”
Section: Introductionmentioning
confidence: 53%
“…Behavioral work points to the presence of separate pathways for signaling S-cone increments and decrements (Krauskopf et al, 1982;Vassilev et al, 2003). There is evidence that the mechanism that detects S-cone decrements has lower sensitivity and a more linear contrast response than the mechanism that detects S-cone increments (Vingrys and Mahon, 1998) (but see Sakurai and Mullen, 2006), and the L-and M-cone contributions to these two mechanisms are thought to differ (McLellan and Eskew, 2000).…”
Section: Relationship To Psychophysicsmentioning
confidence: 99%
“…Vassilev et al 14 used a modified version of Stiles' two-color threshold technique. At eccentricities greater than 5°, they found that the area of spatial summation was greater for S-cone decrements than that for S-cone increments, suggesting that receptive fields are larger for the S-off subsystem.…”
Section: Bistratified Ganglion Cells S-off Ganglion Cellsmentioning
confidence: 99%